Qualitative sonographic assessment of transmural ileal inflammation in Crohn's disease: a comparison with MRI activity score. Issue 7 (July 2021) - Livne, Moran; Amitai, Michal Mariene; Klang, Eyal; Ben Horin, Shomron; Ungar, Bella; Levartovsky, Asaf; Kopylov, Uri; Carter, Dan
Abstract : Background: Intestinal ultrasound (IUS) is an accurate tool for monitoring Crohn's disease. To date, there is no clinically used validated quantitative ultrasonographic score for assessing disease activity. For magnetic resonance enterography (MRE), the magnetic resonance index of activity (MaRIA) is most used. The goal of this study was to devise a new quantitative IUS score for assessing Crohn's disease inflammation, by using a partial MaRIA score as a reference. Methods: This was a retrospective cohort study. The study cohort included patients with Crohn's disease followed between January 2016 and December 2018. Inclusion criteria were age >18 and <3 months between MRE and IUS. Linear/logistic regression was performed for the correlation of ultrasonographic parameters with MaRIA score. Ultrasonograpic features included: bowel wall thickness, disrupted bowel wall stratification, mesenteric fat proliferation, presence of lymph nodes, hypervascularity present on color Doppler flow, and the presence of complications (strictures, inflammatory mass, and fistula). Results: Forty-two patients were included. A stepwise multiple regression model was constructed to predict MaRIA score using ultrasound features. Two variables were found to be independently significant: terminal ileum (TI) thickness ( r  = 0.68, P  = 0.001) and mesenteric fat proliferation ( r  = 0.45, P  = 0.019). A model was constructed as follows: MaRIA = 7 + 2.5 * TI US thickness (mm) + 7 * US fat proliferation (0 = no, 1 = yes). This model has an R 2 of 0.51 for explaining the variability in the results. Conclusions: IUS measurements are significantly correlated with MaRIA score in the terminal ileum and a simple computational model can be constructed.